New Paradigm For Strengthening Women's Political Capacity in the Process of Public Policy Processing - Nur Istiyan Harun (Journal of Governance, 2019)
This study aims to examine more deeply the problems of women politicians in Gorontalo DPRD in Gorontalo Province in the formulation of public policies and seek to provide a new paradigm for strengthening the capacity of women politicians in the process of formulating public policies as a solution to the problems in intent. Women politicians have not been very much involved in the formulation of policies in the parliament, women politicians only become participants when the formulation of policies regarding women is reached and they become connoisseurs when the policies are passed. This problem arises if we try to compare it dichotomically with the existence of women in a quantitative context that is on average proportional to almost half the regional and national population. This research is a qualitative research, using a case study that is intended to explore in-depth explanations and conduct an analysis of the role of women politicians in Gorontalo District Parliament in the period 2014-2019 in formulating public policies. From the results of the study, researchers found that women politicians in Gorontalo District Parliament were not maximal in formulating public policies. Then through Focussed Group Discussion (FGD), Gorontalo women leaders consisting of academics, politicians, women activists, youth organizations and student organizations formulate a paradigm or model that is considered to be able to maximize the role of women in parliament. The paradigm or model or concept referred to is compiled in the form of recommendations that will be given to each political party and Regency / City DPRD and Provincial DPRD in Gorontalo Province and may be used as a reference in strengthening the capacity of women politicians in Gorontalo in particular and Indonesia in general. The recommendation is the provision of political education, the need for a Gender Analysis Pathway (GAP) and Gender Budget Statement (GBS), there must be regulation and characterization.Keywords: New Paradigm, Strengthening Capacity, Women Politicians, Public Policy